Water contents of clinopyroxenes from sub‐arc mantle peridotites. (27th June 2017) - Turner, Michael; Turner, Simon; Blatter, Dawnika; Maury, Rene; Perfit, Michael; Yogodzinski, Gene
Abstract: One poorly constrained reservoir of the Earth's water budget is that of clinopyroxene in metasomatised, mantle peridotites. This study presents reconnaissance Sensitive High‐Resolution, Ion Microprobe–Stable Isotope (SHRIMP–SI) determinations of the H2 O contents of (dominantly) clinopyroxenes in rare mantle xenoliths from four different subduction zones, i.e. Mexico, Kamchatka, Philippines, and New Britain (Tabar‐Feni island chain) as well as one intra‐plate setting (western Victoria). All of the sub‐arc xenoliths have been metasomatised and carry strong arc trace element signatures. Average measured H2 O contents of the pyroxenes range from 70 ppm to 510 ppm whereas calculated bulk H2 O contents range from 88 ppm to 3 737 ppm if the variable presence of amphibole is taken into account. In contrast, the intra‐plate, continental mantle xenolith from western Victoria has higher water contents (3 447 ppm) but was metasomatised by alkali and/or carbonatitic melts and does not carry a subduction‐related signature. Material similar to the sub‐arc peridotites can either be accreted to the base of the lithosphere or potentially be transported by convection deeper into the mantle where it will lose water due to amphibole breakdown. Abstract : We present a new compilation of clinopyroxene water contents from sub‐arc mantle xenoliths. These represent the first application of SHRIMP–SI to water measurements. Abstract : 交代作用を受けたマントルかんらん岩中の輝石が地球内部における水のキャリアーとしてどの程度重要な役割を果たしているのか,  これまで十分に理解されていない. 本研究では,  4ヶ所の沈み込み帯(メキシコ,  カムチャッカ,  フィリピン,  ニューブリテン)およびプレート内部(西ビクトリア)に産する,  交代作用を被ったマントルゼノリス中の輝石を対象に,  SHRIMP‐SIを用いて含水量を予察的に測定した. その結果,  沈み込み帯起源のマントルゼノリス中の輝石含水量は70∼510 ppmであり,  ゼノリス全体としての含水量は 88∼3737 ppmと推定された. 一方,  プレート内部起源のマントルゼノリスの含水量は3447 ppm と推定された. 交代作用を受けたマントル物質は,  リソスフェアの底部で蓄積するか,  もしくは対流によって輸送されたマントル深部において,  角閃石の分解に伴い水を放出している可能性がある.